State of World Population 2001 - United Nations Population Fund (United Nations, 2001)
Each year since 1978, UNFPA has issued a report highlighting new developments in population. Human activity is altering the planet on an unprecedented scale, the report points out. More people are using more resources with more intensity and leaving a bigger footprint on the earth than ever before. This report examines the close links between environmental conditions, population trends and prospects for alleviating poverty in developing countries. It finds that expanding women’s opportunities and ensuring their reproductive health and rights are critically important, both to improve the well-being of growing human populations and to protect the natural world.